Expansão urbana em Áreas de Preservação Permanente - APP: o caso de São Carlos-SP - Delcol, Rafaela Fabiana Ribeiro (2010)
The goal of the current research is to elaborate a study about the urban expansion in Permanently Preserved Areas (PPA) located on the banks of water bodies. The work aims to comprehend historical relationships that exist between cities and their hydro resources. We also analyzed ways humanity is interacting with its environment and how the consequences of this relationship deteriorate the quality of the urban ambient. Tijuco Preto, Gregório and Monjolinho streams located in São Carlos-SP were selected in our studies for the purpose of diagnosing problems endangering APPs, that despite the current regulatory apparatus have a critical and degradation situation, underestimating the treatment by public power and local society for these places.